Effects of DNA Methylation on Progression to Interstitial Fibrosis and Tubular Atrophy in Renal Allograft Biopsies: A Multi‐Omics Approach. Issue 12 (8th July 2017) - Bontha, S. V.; Maluf, D. G.; Archer, K. J.; Dumur, C. I.; Dozmorov, M. G.; King, A. L.; Akalin, E.; Mueller, T. F.; Gallon, L.; Mas, V. R.
Abstract : Progressive fibrosis of the interstitium is the dominant final pathway in renal destruction in native and transplanted kidneys. Over time, the continuum of molecular events following immunological and nonimmunological insults lead to interstitial fibrosis and tubular atrophy and culminate in kidney failure. We hypothesize that these insults trigger changes in DNA methylation (DNAm) patterns, which in turn could exacerbate injury and slow down the regeneration processes, leading to fibrosis development and graft dysfunction. Herein, we analyzed biopsy samples from kidney allografts collected 24 months posttransplantation and used an integrative multi‐omics approach to understand the underlying molecular mechanisms. The role of DNAm and microRNAs on the graft gene expression was evaluated. Enrichment analyses of differentially methylated CpG sites were performed using GenomeRunner. CpGs were strongly enriched in regions that were variably methylated among tissues, implying high tissue specificity in their regulatory impact. Corresponding to this methylation pattern, gene expression data were related to immune response (activated state) and nephrogenesis (inhibited state). Preimplantation biopsies showed similar DNAm patterns to normal allograft biopsies at 2 years posttransplantation. Our findings demonstrate for the first time a relationship among epigenetic modifications and development of interstitial fibrosis, graft function, and inter‐individual variation on long‐term outcomes. Abstract : Through integrative approaches in ex vivo renal allograft biopsies, this study elucidates the role of differential DNA methylation in interstitial fibrosis and tubular atrophy by influencing the expression of genes and upstream regulators involved in pathways that exacerbate organ injury and inhibit repair processes.